TERAPI MUSIK TERHADAP PERUBAHAN TINGKAT KECEMASAN PASIEN KANKER PAYUDARA: LITERATURE REVIEW - Dian Ika Pertiwi; Kadek Ayu Erika; Takdir Tahir (Jurnal Kesehatan, 2022)
Background and aims: Breast cancer is a malignant tumor that grows in the breast tissue. Anxiety has an influence that can worsen health conditions in breast cancer patients. Therefore, this review was conducted to assess the effect of music therapy on changes in anxiety levels of breast cancer patients. Methods: This study was a literature review obtained from six databases, including Scopus, Wiley Online Library, PubMed, Science Direct, DOAJ, and Gray Literature. This review followed the guidelines based on PRISMA 2020. All inclusion articles included English and Indonesian articles and were published in the last five years. Results: Five articles were obtained from this study, each using an intervention research method. Conclusion: Based on these findings, music therapy can be used as an additional intervention to help patients with breast cancer reduce anxiety levels. Keywords: Breast Cancer Patients, Music Therapy, Anxiety Levels